The Flying Horses: From Asia to Europe - Harits, Imron Wakhid; Chudy, Stefan (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2025)
This paper is aimed to compare the mythical animals particularly the unicorns from the different social and historical context across the nation (or culture) as well as their transmission in the world (East and West). The objective of the study is, to examine the Mythical creature particularly the unicorn both in the oral tradition from its historical context such as the mythology of Flying Horse (such as the Unicorn, Pegasus) from India, China, Africa, Indonesia (Madura) and Europe and the Flying Horse (Unicorn, Pegasus) as the character of the fairy tales such as in Carroll’s Through the Looking Glass, Williamson’s The coming of Unicorn, Grimm’s the Brave Little Tailor, and Wiggin and Smith’s the Unicorn and Madura tales Megaremeng.  From the study, it infers that the Flying horse as the mythical animals have the different forms and names in the world. Such as in China it is called as Qilin and in Japan is Kirin. Otherwise at the beginning the Mythology of the the flying horse it can trace back in Greek mythology (Pegasus) and the origin of Unicorn from India and Persia. For examples the unicorn today was not the same as when it was firstly found by Hildegard von Bingen in River Indus. The trade, the war, the mobility of the people like the immigration have contributed to the transformation of the Unicorn in the world. As the mythical animal the Flying horse (unicorn, Pegasus) is one of the most popular mythical creature in the world, thus it is not only mentioned in the cultural history in one country but it is also raised up in some written tales such as in Indonesia and in Scotland where the Flying Horse is as legendary creature used as the symbol of the city and country.